Achieve sales excellence the 7 customer rules for becoming the new sales professional - Stevens, Howard; Kinni, Theodore B. (Avon, Mass. : Platinum Press, 2007)
Achieve sales excellence examines the new paradigm of business-to-business sales. Based on the results of an innovative, fourteen-year study, this book offers unmatched insight on sales performance issues and the practices sales professionals and organizations must embrace to be a world-class sales force.
Keywords: Industrial marketing; Customer relations; Customer loyalty; Selling -- Study and teaching